Chemical and hydrodynamic alignment of an enzyme - Adeleke-Larodo, T; Agudo-Canalejo, J; Golestanian, R (AIP Publishing, 2019)
Motivated by the implications of the complex and dynamic modular geometry of an enzyme on its motion, we investigate the effect of combining long-range internal and external hydrodynamic interactions due to thermal fluctuations with short-range surface interactions. An asymmetric dumbbell consisting of two unequal subunits, in a nonuniform suspension of a solute with which it interacts via hydrodynamic interactions as well as non-contact surface interactions, is shown to have two alignment mechanisms due to the two types of interactions. In addition to alignment, the chemical gradient results in a drift velocity that is modified by hydrodynamic interactions between the constituents of the enzyme.